Licensing effects of inflammatory factors and TLR ligands on the regenerative capacity of adipose-derived mesenchymal stem cells - Szűcs, Diána; Monostori, Tamás; Miklós, Vanda; Páhi, Zoltán G.; Póliska, Szilárd; Kemény, Lajos; Veréb, Zoltán (Frontiers in Cell and Developmental Biology, 2024)
Adipose tissue-derived mesenchymal stem cells are promising contributors to regenerative medicine, exhibiting the ability to regenerate tissues and modulate the immune system, which is particularly beneficial for addressing chronic inflammatory ulcers and wounds. Despite their inherent capabilities, research suggests that pretreatment amplifies therapeutic effectiveness. Our experimental design exposed adipose-derived mesenchymal stem cells to six inflammatory factors for 24 hours. We subsequently evaluated gene expression and proteome profile alterations and observed the wound closure rate post-treatment. Specific pretreatments, such as IL-1β, notably demonstrated an accelerated wound-healing process. Analysis of gene and protein expression profiles revealed alterations in pathways associated with tissue regeneration. This suggests that licensed cells exhibit potentially higher therapeutic efficiency than untreated cells, shedding light on optimizing regenerative strategies using adipose tissue-derived stem cells.